2020
DOI: 10.3389/fmolb.2020.599340
|View full text |Cite
|
Sign up to set email alerts
|

m5C RNA Methylation Primarily Affects the ErbB and PI3K–Akt Signaling Pathways in Gastrointestinal Cancer

Abstract: 5-Methylcytosine (m5C) is a kind of methylation modification that occurs in both DNA and RNA and is present in the highly abundant tRNA and rRNA. It has an important impact on various human diseases including cancer. The function of m5C is modulated by regulatory proteins, including methyltransferases (writers) and special binding proteins (readers). This study aims at comprehensive study of the m5C RNA methylation-related genes and the main pathways under m5C RNA methylation in gastrointestinal (GI) cancer. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…RNA m5C, characterised by the addition of a methyl group at the carbon-5 position of the cytosine base, has been detected not only in rRNA and tRNA but also in mRNA by high-throughput sequencing-based transcriptome-wide mapping approaches. 7 m5C is well-conserved and dynamically regulated in cellular mRNAs, and it localises to the untranslated regions (UTRs) of mRNA transcripts. It may influence a wide variety of biological functions by regulating RNA metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…RNA m5C, characterised by the addition of a methyl group at the carbon-5 position of the cytosine base, has been detected not only in rRNA and tRNA but also in mRNA by high-throughput sequencing-based transcriptome-wide mapping approaches. 7 m5C is well-conserved and dynamically regulated in cellular mRNAs, and it localises to the untranslated regions (UTRs) of mRNA transcripts. It may influence a wide variety of biological functions by regulating RNA metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…We studied the potential carcinogenic mechanisms and pathways of these m 5 C RNA methylation regulators in ccRCC by conducting a KEGG analysis, the results agree with published data suggesting that the PI3K/AKT signaling pathway is involved in these mechanisms. 30 , 31 A recent study demonstrated that the PI3K/AKT signaling pathway is implicated in proliferation and migration processes in ccRCC, 32 laying a theoretical foundation for further studies on the function of m 5 C RNA methylation regulators and the mechanisms underlying their regulatory effects. These findings confirm to some extent that m 5 C RNA methylation regulators participate in the progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cytosine DNA methyltransferase Dnmt2 is frequently found to be mis-regulated or mutated in tumors ( Elhardt et al, 2015 ; Wang et al, 2020 ). RNA cytosine-5 methylation has also been shown to be important for normal development and cellular stress responses, in addition to cancer ( Blanco et al, 2011 ; Metodiev et al, 2014 ; Popis et al, 2016 ; Gkatza et al, 2019 ; Xiang et al, 2020 ). Our data suggests that alterations in post-transcriptional modification of RNA might be an early event during oncogene induced preneoplastic development.…”
Section: Discussionmentioning
confidence: 99%